Features of ion generation by a picosecond laser in the range of 1011–1013 W cm−2 power densities. (11th November 2021) - Kondrashev, S; Beebe, E; Kanesue, T; Okamura, M; Scott, R
Abstract: Picosecond lasers (ps-lasers) have significant advantages for the generation of low charge state ions compared to nanosecond lasers because the influence of heat conductivity on a solid target is almost negligible in the case of ps-laser ablation for laser pulse durations less than 10 ps. However, there is no comprehensive data on ion yields for different elements and target irradiation conditions for laser power densities at the target surface around and below 10 13 W cm −2, which is of interest to our study of such plasmas as a source of low charge state ions for various applications, particularly for external injection of those ions into an Electron Beam Ion Source (EBIS). We investigated ion generation from Al, Ti, Cu, Nb and Ta target elements by a ps-laser with power densities in the range of 10 11 –10 13 W cm −2 at the target surface. A ps-laser with 1.27 mJ maximum energy within an 8 ps pulse and repetition rate up to 400 Hz has been used to generate a laser-ablated plasma. Dependencies of ion current versus time, total charge of registered ions as well as ion kinetic energy distributions are characterized using a Faraday cup. Significant difference in ion current dynamics between first, second and following shots onto the same target spot was found for all five target elements. The total charge of ions registered by the Faraday cup increases linearly with increasing laser pulse energy and is almost independent of the target element and number of shots onto the same target spot for all five target elements studied. The results obtained give us a basis for specification and design of the source of low charge state ions for external injection into EBIS.